The influence of individuals, workload, and physical work environment on work stress of nurses at Mamuju Regional General Hospital - Syam, Muh. Isra' Suryadi; Muis, Masyitha; Naiem, M. Furqaan; Russeng, Syamsiar S.; Rivai, Fridawaty (Edelweiss Applied Science and Technology, 2026)
Occupational stress in nurses is an important problem because it can impact the health of the workforce, patient safety, and the quality of hospital services, especially in working conditions with high physical and mental demands. This study determines the influence of individual factors, workload, and physical work environment on work stress in nurses at Mamuju Regional General Hospital. This study used a quantitative cross-sectional design with a total sample of 121 nurses, measuring work stress using a cocorometer, mental workload using NASA-TLX, and lighting and temperature as the physical work environment, and analyzed using the chi-square test and ordinal logistic regression. Bivariate analysis showed a significant influence between mental workload on job stress (p=0.003<0.005), and work environment temperature on job stress (p=0.002<0.005). Mental workload and workplace temperature significantly affect nurses' work stress, with high mental workload and non-standard temperatures increasing the risk of stress, while individual factors and lighting have no significant effect. Mental workload and work environment temperature conditions are dominant factors that influence nurses' work stress, so that proportional workload management and control of physical work environment conditions are important strategies in preventing work stress and improving the quality of nursing services.